The Role of Foreign Direct Investment in Economic and Social Development in Libya - Ehmaida, Abobaker; Jajuga, Prof. Krzysztof (The journal of contemporary issues in business and government, 2022)
Investments in governments are funds injected into action plans of a government to propel it to development (Kumari, 2012). Libya needs such investments to grow in different sectors of development that are divided into action plans. Furthermore, the action plans are designed into goals that are stipulated to be achieved in certain duration of time and in stages that can be monitored. Therefore, it is crucial to learn the process of receiving foreign direct investment and its determinant in Libya’s case. Also understanding the effects of foreign direct investment to the transition of renewable energy in Libya is crucial. The research project is based on the role of foreign direct investment in economic and social development in Libya taking the case of transition to renewable energy in Libya in the future. The foreign direct investment enables both positive and negative aspect in country that enables one to judge its effect to Libya and get the best insight of the investment (Abushhewa&Zarook, 2016). Additionally, the path taken by many countries on renewable energy has forced Libya to embrace such changes and foster it in the country in different ways. A lot of gains have been exhibited through the FDI since there are job opportunities being created, a new economic path has also been set by the Libyan government, and also ownership of property has increased thus increasing the economic levels (Abushhewa&Zarook, 2016). The study will use a descriptive approach that explains the role of foreign direct investment in economic and social development in Libya and how it directly affects the transition to renewable energy. The approach creates a perfect understanding of FDI, its determinant, the foreign investors of Libya, policies set to encourage FDI and how it contributes to the transition to renewable energy in Libya.